A Novel Blood‐Based Colorectal Cancer Diagnostic Technology Using Electrical Detection of Colon Cancer Secreted Protein‐2. Issue 11 (16th April 2019) - Jeun, Minhong; Lee, Hyo Jeong; Park, Sungwook; Do, Eun‐ju; Choi, Jaewon; Sung, You‐Na; Hong, Seung‐Mo; Kim, Sang‐Yeob; Kim, Dong‐Hee; Kang, Ja Young; Son, Hye‐Nam; Joo, Jinmyoung; et al.
Abstract: Colorectal cancer (CRC) is the second‐leading cause of cancer‐related mortality worldwide, which may be effectively reduced by early screening. Colon cancer secreted protein‐2 (CCSP‐2) is a promising blood marker for CRC. An electric‐field effect colorectal sensor (E‐FECS), an ion‐sensitive field‐effect transistor under dual gate operation with nanostructure is developed, to quantify CCSP‐2 directly from patient blood samples. The sensing performance of the E‐FECS is verified in 7 controls and 7 CRC samples, and it is clinically validated on 30 controls, 30 advanced adenomas, and 81 CRC cases. The concentration of CCSP‐2 is significantly higher in plasma samples from CRC and advanced adenoma compared with controls (both P < 0.001). Sensitivity and specificity for CRC versus controls are 44.4% and 86.7%, respectively (AUC of 0.67), and 43.3% and 86.7%, respectively, for advanced adenomas (AUC of 0.67). CCSP‐2 detects a greater number of CRC cases than carcinoembryonic antigen does (45.6% vs 24.1%), and the combination of the two markers detects an even greater number of cases (53.2%). The E‐FECS system successfully detects CCSP‐2 in a wide range of samples including early stage cancers and advanced adenoma. CCSP‐2 has potential for use as a blood‐based biomarker for CRC. Abstract : This work proposes a highly sensitive electric field‐effect colorectal sensor (E‐FECS) system that is stable and sensitive enough to detect colon cancer secreted protein‐2 (CCSP‐2) directly from patient plasma samples. In combination with the E‐FECS system, plasma CCSP‐2 can detect nearly half of cancers and it is equally sensitive for the detection of both early and overtly metastatic cancers.